Endometrial small extracellular vesicles regulate human trophectodermal cell invasion by reprogramming the phosphoproteome landscape - Monique Fatmous; Monique Fatmous; Alin Rai; Alin Rai; Alin Rai; Alin Rai; Qi Hui Poh; Qi Hui Poh; Qi Hui Poh; Lois A. Salamonsen; Lois A. Salamonsen; David W. Greening; et al. (Frontiers in Cell and Developmental Biology, 2022)
A series of cyclical events within the uterus are crucial for pregnancy establishment. These include endometrial regeneration following menses, under the influence of estrogen (proliferative phase), then endometrial differentiation driven by estrogen/progesterone (secretory phase), to provide a microenvironment enabling attachment of embryo (as a hatched blastocyst) to the endometrial epithelium. This is followed by invasion of trophectodermal cells (the outer layer of the blastocyst) into the endometrium tissue to facilitate intrauterine development. Small extracellular vesicles (sEVs) released by endometrial epithelial cells during the secretory phase have been shown to facilitate trophoblast invasion; however, the molecular mechanisms that underline this process remain poorly understood. Here, we show that density gradient purified sEVs (1.06–1.11 g/ml, Alix+ and TSG101+, ∼180 nm) from human endometrial epithelial cells (hormonally primed with estrogen and progesterone vs. estrogen alone) are readily internalized by a human trophectodermal stem cell line and promote their invasion into Matrigel matrix. Mass spectrometry-based proteome analysis revealed that sEVs reprogrammed trophectoderm cell proteome and their cell surface proteome (surfaceome) to support this invasive phenotype through upregulation of pro-invasive regulators associated with focal adhesions (NRP1, PTPRK, ROCK2, TEK), embryo implantation (FBLN1, NIBAN2, BSG), and kinase receptors (EPHB4/B2, ERBB2, STRAP). Kinase substrate prediction highlighted a central role of MAPK3 as an upstream kinase regulating target cell proteome reprogramming. Phosphoproteome analysis pinpointed upregulation of MAPK3 T204/T202 phosphosites in hTSCs following sEV delivery, and that their pharmacological inhibition significantly abrogated invasion. This study provides novel molecular insights into endometrial sEVs orchestrating trophoblast invasion, highlighting the microenvironmental regulation of hTSCs during embryo implantation.